Synthesis of Magnetite-Reduced Graphene Oxide Nanocomposite as a Recyclable Demulsifier for Crude Oil-In-Water Emulsion - YAU, XIN HUI (2019)
Water–oil emulsion is a type of oily wastewater discharged by the petroleum industry. It is difficult to break up by physical means, thereby causing environmental problems and attracting global concern. Chemical demulsifiers are limited by their toxicity and non-environmentally friendly characteristics.